Separation and Extraction Micro Amount of Cadmium (II) and Mercury (II) with Liquid Anion Exchange Method - Jawad, S. K.; Hameed, S. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
For extraction chloro anion complexes of Cd2+ and Hg2+ used many organic agents as extractant according to liquid ion exchange method such as Î±-Naphthyl amine (Î±-NA), 4-Amino benzoic acid (4-ABA), 2-[(4-Carboxy methyl phenyl) azo]-4,5-diphenyl imidazole (4CMePADPI) and Cryptand (C222). This study includes definition hydrochloric acid concentration in aqueous phase and shaking with organic phase necessary for extraction as well as shaking time, organic solvent effect, interferences and alkaline salt effect. Thermodynamic showed the ion exchange reaction was exothermic for Î±-NA, C222 and endothermic for 4-ABA, 4-CMePADPI for extraction CdCl4=, but for extraction HgCl4= was exothermic with 4-ABA, 4CMePADPI and C222 but endothermic with Î±-NA. In addition stoichiometry showed the ion pair complex extracted was 1:1:1 Cation: Ligand: Anion